Inflammation and asthma control in children with comorbid obstructive sleep apnea. Issue 9 (3rd June 2018) - Rogers, Valerie E.; Bollinger, Mary E.; Tulapurkar, Mohan E.; Zhu, Shijun; Hasday, Jeffrey D.; Pereira, Kevin D.; Scharf, Steven M.
Abstract: Objectives: A bi‐directional relationship exists between asthma and obstructive sleep apnea (OSA) in which presence of one is associated with increased prevalence and severity of the other. Our objective was to determine whether OSA accounted for differences in airway and systemic inflammation in asthmatic children and whether inflammation was associated with asthma control. We hypothesized that greater severity of SDB would correlate with increased upper airway and systemic inflammation and result in reduced asthma control. Methods: Non‐obese children aged 4‐12 years with persistent asthma, with or without OSA were recruited. Asthma control was measured with the Childhood Asthma Control Test. Children underwent polysomnography and blood sampling, and children with OSA underwent clinically indicated adenotonsillectomy. Tonsils and sera were analyzed for 11 cytokines. Results: Twenty‐seven children (20 with OSA, seven without OSA) participated, mean age 7.9 years, 55.6% female, 92.6% African American. Levels did not differ for any cytokine between children with and without OSA. Lower nadir oxygen saturation was associated with higher levels of tonsil TNF‐α ( P < 0.001) and IL‐10 ( P < 0.05). Higher REM‐related apnea‐hypopnea index was associated with higher levels of tonsil TNF‐α ( P < 0.05). Children with uncontrolled asthma had significantly higher levels of serum IL‐10, IL‐13, and TNF‐α, and tonsil TNF‐α (all P < 0.05) than well‐controlled asthmatic children. There was no association between OSA, or any polysomnography variable, and asthma control. Conclusions: Despite the presence of OSA‐associated airway inflammation, and asthma control‐associated airway and systemic inflammation, OSA was not related to level of asthma control in this non‐obese, largely minority, low income sample.